Supply and Demand Characteristics of Palm Kernel Shell as a Renewable Energy Source for Industries - Handaya Handaya; Herry Susanto; Dikky Indrawan; Marimin Marimin (International Journal of Renewable Energy Development, 2022)
Depleting stockpile of fossil fuels and rising global temperature due to the greenhouse effect are probably the two most threatening factors to civilization sustainability. Converting biomass into a readily available energy source will help reduce dependency on fossil fuels, whilst at the same time moderating greenhouse gas emmissions due to its carbon neutrality. Palm oil industry is the largest source of biomass in Indonesia and the available quantity to be utilized is growing inline with the steady growth of the generating industry. Among various wastes from palm oil processing, palm kernel shell is an oil palm biomass with high potential to be applied as a source of energy, given its high caloric value and distinctive physical properties. This source of renewable energy can be utilized by industries with thermal conversion processes. As a prerequisite, a feasibility study on technical, environmental, and economic aspects needs to be carried out. From long term perspective, supply, demand, and regulatory situational analysis will also be required. Lastly, a review on the existing palm kernel shell supply chain will help to understand its current situation. Based on literature studies and field observations, we have identified supply and demand characteristics that will be valuable in constructing an effective, efficient, and sustainable supply chain model of palm kernel shell. Understanding these characteristics is a precursor in realizing this massive potential of renewable energy source in the industrial context.